Moral Considerations of Students in Taking Online Loans: Between Needs and Desires - Ratna Kartika Wati; Ani Kusbandiah; Indriati Amarini (Jurnal Moral Kemasyarakatan, 2025)
This study examines students' morality in decision-making regarding online loans. The purpose of this study is to identify factors that influence students' decisions to take online loans and analyze the role of morality in this process. This study uses a combination of qualitative and quantitative methodologies, aiming to provide deeper insights into the social and economic impacts of online loans on students. Data collection techniques include surveys, in-depth interviews, and case study analysis. In the context of the increasingly widespread phenomenon of online loans, especially among students, this study identifies several factors that influence their decisions to borrow. This study also links its findings to the Theory of Planned Behavior (TPB) and Moral Theory. Individual and collective morality play an important role in decision-making regarding online loans. Collective morality, which includes the norms and values ​​of social groups, also influences online loan decisions. Students' involvement with online loans has a significant impact. In the short-term, students often experience stress and anxiety due to debt pressure. In the long-term, it can disrupt education and create a cycle of poverty.